Applying medical truths to qualitative, descriptive and statistical gender spotting analysis of telephone conversations and dialogues of elderly population speech in Muriel Spark’s novel Memento Mori, revisiting the deficit and genderlect models combined - Majetic, Senka (Eximia, 2023)
The mixed-method approach, combined with the deficit model language assumptions indicators analysis, will be presented. The discourse analysis scheme (condensed from "You Just Don’t Understand" by Deborah Tannen), fulfilled with a discussion which is, in fact, a descriptive analysis on semantic, syntactic and pragmatic levels, mentioning the distribution and frequency of word classes, as well as the selected "female speech inclined speech act" (asking questions) analysis, are going to be used to confirm the directional hypothesis that female language dominates in the novel "Memento Mori" by Muriel Spark. Due to the current gender-oriented linguists’ suggestions that the language of minorities, transgender persons, and homosexuals should be researched today (not, by the gender studies, overexploited language of a 30-year-old white woman) the elderly population vernacular, used in the novel "Memento Mori", is going to be shown, revisiting the deficit and genderlect models and comparing the discourse with the contemporary human communication practices.